2012
DOI: 10.3390/molecules17055972
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Curcumin-Loaded Liposomes and Evaluation of Their Skin Permeation and Pharmacodynamics

Abstract: This study aimed to investigate the in vitro skin permeation and in vivo antineoplastic effect of curcumin by using liposomes as the transdermal drug-delivery system. Soybean phospholipids (SPC), egg yolk phospholipids (EPC), and hydrogenated soybean phospholipids (HSPC) were selected for the preparation of different kinds of phospholipids composed of curcumin-loaded liposomes: C-SPC-L (curcumin-loaded SPC liposomes), C-EPC-L (curcumin-loaded EPC liposomes), and C-HSPC-L (curcumin-loaded HSPC liposomes). The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
134
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(149 citation statements)
references
References 27 publications
12
134
2
1
Order By: Relevance
“…Faster diffusion of curcumin without liposomes compared to that embedded in liposomes demonstrates the sustained release of entrapped curcumin. Thus, liposomes can act as effective drug delivery systems, ensuring the sustained and prolonged release of curcumin 38,65 . Initially, a burst release was recorded for curcumin in all formulations which occurred because of the release of curcumin adsorbed on the liposome surface as well as the free curcumin molecules.…”
Section: Fluorescence Anisotropy Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Faster diffusion of curcumin without liposomes compared to that embedded in liposomes demonstrates the sustained release of entrapped curcumin. Thus, liposomes can act as effective drug delivery systems, ensuring the sustained and prolonged release of curcumin 38,65 . Initially, a burst release was recorded for curcumin in all formulations which occurred because of the release of curcumin adsorbed on the liposome surface as well as the free curcumin molecules.…”
Section: Fluorescence Anisotropy Studiesmentioning
confidence: 99%
“…A dialysis bag 12 kDa molecular weight cut-off, Sigma-Aldrich was used. While the donor medium contained 5 mL curcumin-loaded liposomes or aqueous curcumin solution control , the receptor compartment contained 20 mL phosphate-buffered saline buffer pH 7.4 with 0.5 Tween-80 and 20 ethanol v/v as a sink at 37 38 . At specific time intervals, 3 mL receptor medium was withdrawn with concomitant addition of the same volume of fresh medium and the aliquots were analyzed colorimetrically.…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, greater retention was observed, in the µg/g range; results were expressed in grams of skin because non-dermatomed pig ear skin has variable thickness (0.95 -1.45 mm in this study). In another investigation, skin retention of liposomeencapsulated curcumin was in the µg/cm 2 range in experiments with a duration of up to 50 hours (Chen et al, 2012). Parameters that affect the skin permeation of a substance and should be taken into account include the size of the molecule, its polarity, and its partition coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, zeta potential is a measure of the charge on the surface of a particle in a specific liquid medium [8]. Stable nanoparticle suspensions should have a zeta potential value of <−30 mV or more than +30 mV [9]. Thus, suspensions must have a higher repulsive force and a stable system to prevent the aggregation of the particle.…”
Section: Particle Size and Zeta Potential Measurementmentioning
confidence: 99%